Internal and External Morphological Characteristics of the Medicinal Leech Species Hirudo sulukii and Hirudo verbana - Sağlam, Naim (Galenos Publishing House, 2019)
Objective: The aim of this study was to investigate the internal and external morphological structures of two species of medicinal leeches (Hirudo sulukii and Hirudo verbana). Methods: Leech specimens were collected from various regions of Turkey between the years of 1995-2016. The leeches were first examined alive and later were stunned with 10% ethyl alcohol and fixed in 70% ethyl alcohol or 4% formaldehyde. After fixation, the internal morphology of leeches was examined by dissecting them under a stereo microscope. Results: Both species of leeches are dorso-ventrally flattened. H. verbana is larger and broader than H. sulukii. H. sulukii has black, segmentally-arranged united ellipsoid and elongated spots, and a pair of zigzagged black longitudinal stripes in the dorso-lateral area of its body. The ventral surface of H. sulukii is greenish to brown in colour and has a small number of irregular black spots. H. verbana has broad and diffuse, paramedian, orange stripes on the dorsal surface. Ventrally, H. verbana has a greenish to yellow colour, and it is characterized by a pair of black ventro-lateral stripes. Conclusion: Two of the six leech species (Hirudo sulukii and Hirudo verbana) belonging to the genus Hirudo found in the world are found in Turkey. These two leech species show significant differences from each other, morphologically. © 2019 Turkish Society for Parasitology.
Tıbbi Sülük Türleri Hirudo sulukii ve Hirudo verbana’nın İç ve Dış Morfolojik Özellikleri
Keywords: Hirudo sulukii; Hirudo verbana; Medicinal leeches; morphological structure